Modelling the toxicity of copper and zinc to wheat and other crops and incorporation of the results into a proposed framework to derive biosolids guidelines - Warne, M.; Heemsbergen, D.; McLaughlin, M.; Stevens, D.; Cozens, G.; Broos, K.; Barry, G.; Bell, M.; Whatmuff, M.; Nash, D.; Pritchard, Deborah; Penney, N. (Australian Water Association, 2006)
The application of biosolids to land can have both beneficial and detrimental environmentaleffects. The positive effects can arise from nutrients and organic carbon in the biosolids whilethe negative effects generally arise because of the contamination associated with biosolids(e.g. Broos et al., 2006; Heemsbergen et al., 2006; McLaughlin et al., 2006) but can also arisedue to excessive ammonia (Whatmuff et al., 2006). Therefore, any regulatory guidelinesdeveloped to manage the land application of biosolids must be able to enhance the beneficialeffects and minimise the deleterious effects.